Economic Performance Measure for Creating Shareholder’s Value: A Study of Selected Manufacturing Companies in Colombo Stock Exchange - Thasika, Y.; Dilogini, S.; Nishanthini, A. (South Eastern University of Sri Lanka, 2016)
This study intends to analyses the importance of economic performance measure for creating shareholder’s value. There is dearth of literature on economic value added in Asian counties including Sri Lanka. To the best of the researcher’s knowledge, this research is the first attempt to investigate economic performance on shareholder’s value creation in emerging market. This study lies within the positivism methodology and adopts a quantitative approach. Accordingly, secondary data derived from the annual financial reports of selected 10 manufacturing firms during the period of 2010-15, using the CSE’s databases. The study reveals that Economic Value Added (EVA) has a negative and less significant relationship with shareholder’s value creation. Whilst, it influences on shareholder’s value creation more than half percentage. EVA has been able to gain attention of shareholder’s value creation. It is able to depict the true profitability the company and more investment by investors, however there have been very little research conducted on EVA and shareholder’s value in Sri Lanka. EVA is vital, in that if not properly planned, investment can have disastrous financial and performance implications.
Keywords: Economic value added; Shareholder’s value creation; Performance measure